Java Gently, Third Edition - Bishop, Judith (Pearson Business, 2001)
The third edition of Java Gently by Judith Bishop continues the successful approach that made earlier versions popular and has added improvements which will maintain its place as a worldwide bestseller. Java Gently teaches the reader how to program and how to do it in the best possible style in Java. In the process, it details the fundamental structures of the Java 2 language and most of its core libraries and utilities. The book covers object-orientation, software design, structured programming, graphical user interfacing, event-driven programming, networking, and an introduction to data structures. Java Gently gets students started on meaningful input/output in an object-oriented way without hiding basic concepts. Applets, multimedia, graphics, and networking are introduced as students encounter and can handle classes, objects, instantiation, and inheirtance. The textbook's excellent pedagogy reinforces understanding and demonstrates good programming practice. The three kinds of diagrams include class, form, and algorithm diagrams. The fully worked examples have been carefully chosen to illustrate recently introduced concepts and solve real-world problems in a user-friendly manner. End of chapter multiple choice quizzes and problems allow students to test their comprehension of the material.